Anaesthesia-related complications and side-effects in TAVI: a retrospective study in Germany. Issue 4 (1st May 2019) - Goldfuss, Sophia; Wittmann, Sigrid; Würschinger, Fabian; Bitzinger, Diane; Seyfried, Timo; Holzamer, Andreas; Fischer, Marcus; Camboni, Daniele; Sinner, Barbara; Zausig, York Alexander
Abstract : Objectives: This study was performed to analyse anaesthesia-related complications and side effects in patients undergoing transcatheter aortic valve implantation (TAVI) under general anaesthesia. Design: Retrospective study. Setting: The study was performed as a single-centre study in a hospital of tertiary care in Germany. Participants: All 853 patients, who underwent TAVI at the Universitätsklinikum Regensburg between January 2009 and July 2015, were included. 52.5% were female patients. Primary and secondary outcome measures: We gathered information, such as recent illness, vital parameters and medication administered during the intervention and postoperatively for 12 hours. We analysed all anaesthesia-related complications and anaesthesia-related side effects that occurred during the intervention and entire hospital stay. Results: We analysed all 853 TAVI procedures. The mean patient age was 79 ± 6 years. In 99.5% of cases, we used volatile-based anaesthesia. 2.8% (n=24; transfemoral (TF): n=19 [3.8%]; transapical (TA): n=5 [1.4%]) of all cases suffered from anaesthesia-related complications. 819 (TF: n=447; TA: n=372) anaesthesia-related side effects occurred in 586 (68.7%, TF: n=325 [64.2%], TA: n=261 [75.2%]) patients. Neither the complications nor the side effects had any serious consequences. Intraoperative hypothermia in 44% of cases (TF: n=202 [39.9%]; TA: n=173 [49.9%]) and postoperative nausea and vomiting in 27% (n=232; TF: n=131 [25.9%], TA: n=101 [29.1%]) of cases were the most common anaesthesia-related side effects. Conclusion: In this study, serious anaesthesia-related complications were rarely seen, and non-critical anaesthesia-related side effects could have been avoided through consistent prophylaxis and management. Therefore, despite their high anaesthetic risk, general anaesthesia is justifiable in patients who underwent TAVI.